2017
DOI: 10.18632/oncotarget.16248
|View full text |Cite
|
Sign up to set email alerts
|

The miR-124-p63 feedback loop modulates colorectal cancer growth

Abstract: Among the diverse co-regulatory relationships between transcription factors (TFs) and microRNAs (miRNAs), feedback loops have received the most extensive research attention. The co-regulation of TFs and miRNAs plays an important role in colorectal cancer (CRC) growth. Here, we show that miR-124 can regulate two isoforms of p63, TAp63 and ΔNp63, via iASPP, while p63 modulates signal transducers and activators of transcription 1 (STAT1) expression by targeting miR-155. Moreover, STAT1 acts as a regulator of CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
(69 reference statements)
1
21
0
Order By: Relevance
“…As described in our research, we showed that noncoding RNAs were involved in breast cancer metastasis and miR-124 inhibited cell proliferation in breast cancer [16][17][18]. Consistent with our findings, miR-124 was decreased in colorectal tissue samples and was correlated with adverse clinical indicators and poor patient survival time [19][20][21]. Downregulation of plasma miR-124 expression was a predictive biomarker for prognosis of glioma [10,22].…”
Section: Discussionsupporting
confidence: 89%
“…As described in our research, we showed that noncoding RNAs were involved in breast cancer metastasis and miR-124 inhibited cell proliferation in breast cancer [16][17][18]. Consistent with our findings, miR-124 was decreased in colorectal tissue samples and was correlated with adverse clinical indicators and poor patient survival time [19][20][21]. Downregulation of plasma miR-124 expression was a predictive biomarker for prognosis of glioma [10,22].…”
Section: Discussionsupporting
confidence: 89%
“…MicroRNAs (miRNAs) are non-coding RNA molecules with a length of 18-22 nt. They regulate gene expression through targeted binding of the 3' untranslated region (3'UTR) terminal of mRNA molecules (4). In recent years, numerous scholars have confirmed that miRNA molecules in tumor tissue are novel markers for clinical tumor diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, retinoic orphan receptor-γ (RORγ) and signal transducer and activator of transcription 3 (STAT3)are the transcription factors responsible for Th17 differentiation andstabilization.Gerogios et al demonstrated that miR-124 could promote the children UC and pathogenesis by regulating the expression and phosphorylation of STAT3, but special cell type was not involved [14]. The previous study also demonstrated that miR-124 depression was related to carcinogenesis, and development by targeting different gene [23,24,25].These observations suggested that miR-124 played an key role in colitis and sporadic colon cancer.In our present study, we focused on the miR-124 function in Th17 cell and found that miR-124 could inhibit the polarization of Th17 cell and promote the transition of Th17 to treg in colitis and colitis related colon cancer by targeting stat3 gene.These results are consistent with downregulation of miR-124 developingintestinal failure with M1 macrophage phenotype by targeting stat3 and acetylcholinesterase (AChE). We believe that in the absence of miR-124 signaling cascade, the presence of intestinal commensal bacteria will drive intestinal CD4 + T helper cells toward Th17 cell polarization, resulting in a hyper-in ammatory response with associated tissue damage and pathogenesis.…”
Section: Discussionmentioning
confidence: 97%